Genomic analysis of a novel ST11(PR34365) Clostridioides difficile strain isolated from the human fecal of a CDI patient in Guizhou, China - Yang Ying; Shu Luhong; Ling Ping; Yang Junyi; Shao Ruirui; Cheng Yumei; Luo Shanshan; Wei Xinglang; Guan Zhizhong; Chen Zhenghong; Liao Jian; Qi Xiaolan; et al. (Open Life Sciences)
Clostridioides difficile is a pathogen that causes pseudomembranous colitis with antibiotic-associated diarrhea. The epidemiology and molecular evolution of C. difficile may differ among different geographic regions, and mining its genomic information can help to understand the epidemiology and molecular evolution of C. difficile and focus on its transmission mode. A C. difficile strain denoted WXL8 was isolated from a human fecal sample from a patient in the intensive care unit, and its physiology and genomic sequence were determined. The total genome size of WXL8 was 4,119,929 bp, and the GC content was 27.97%. The multilocus sequence typing results indicated that WXL8 is strain type 11 (ST11), a genotype widely present in livestock. The WXL8 was located in clade 5 of ST11. The ribotype of WXL8 was a novel ribotype (PR34365). It is the first report of the ST11 (PR34365) strain. Comparative genomic analysis between WXL8 and the other four high-virulence strains (CD630, CDBR81, CDS-0253, and CDR20291) showed differences in gene arrangement, indicating the uniqueness of C. difficile WXL8. In the present study, a novel ribotype (PR34365) ST11 strain of C. difficile was isolated from a patient with diarrhea in Guizhou, China. Our findings suggest that zoonotic CDI should receive more clinical attention.